Technical and financial analysis of 1 GT Gill net fishing in Teluk Lancar Village, Bantan District, Bengkalis Regency, Riau Province - Alhafis, Mhd; Zain, Jonny; Isnaniah, Isnaniah (South East Asian Marine Sciences Journal, 2024)
This research was conducted in February 2023 at Teluk Lancar Village, Bantan District, Bengkalis Regency, Riau Province, to know fishermen's techniques in carrying out fishing activities using gill nets with 1 GT boats and how the business feasibility of fishermen using gill nets with boats 1 GT using the survey method. The results showed that the fishermen's technique of operating gill nets in Teluk Lancar Village measured the water's depth; after that, the net was used and thrown to the right of the ship while moving backward (setting). Furthermore, within 1 or 2 hours, the crew lifted the nets in the water onto the ship and moved forward. Fishermen's investment in business activities is IDR 27,600,000.00. The total costs incurred in fishing business activities amount to IDR 92,190,000.00/year, the income received by fishermen is IDR 113,352,000.00/year, the revenue that fishermen have obtained is IDR 21,162,000.00/year, the results of calculating business feasibility based on the formula Revenue Cost of Ratio (R/C), Payback Period of Capital (PPC), and Financial Rate of Return (FRR) this business is feasible to continue and also develop.